SOME CHEMICAL COMPOUNDS OF RED BEET AND THEIR SIGNIFICANCE (Scientific journal of the Fergana State University, 2023)
The article provides information about some of the chemical compounds in red beet and their biological significance. Beetroot is rich in compounds that are very useful for human health, it contains vitamins, minerals, phenolic compounds, carotenoids, nitrates, ascorbic acid, betalain pigments and many other biologically active compounds. This article discusses the carbohydrates, amino acids, vitamins, minerals in plants and their functions in the body.